Nonlinearities of hardware-in-the-loop environment affecting turning process emulation. (October 2020) - Beri, Bence; Miklos, Akos; Takacs, Denes; Stepan, Gabor
Abstract: In hardware-in-the-loop (HIL) experimental environment, a local softening character of the emulated cutting force is observed during the emulation of turning, which affects the stability properties of the process. The real workpiece is substituted by a dummy one that is clamped to the real main spindle. It is excited in the lateral direction by an electromagnetic actuator. The position of the dummy workpiece is monitored by contactless laser-based sensors to close the feedback loop. The previous and the present position of the workpiece is stored to attain the effect of surface regeneration. The desired cutting force characteristic is calculated by means of a high performance real-time computer. The experimental results gained for the linear loss of stability of the process and for the spindle speed dependent dynamics leads to the conclusion that the dominant frequency decreases as the virtual depth of cut and thus the emulated cutting force increases. This is identified for a wide range of real spindle speeds and virtual depth of cuts. The measurement results are supported by theoretical stability analysis and the variation of the dominant frequency is tracked by means of the unexpected local softening nonlinearity of the electromagnetic actuator emulating the real cutting forces, which are also confirmed analytically. These results are needed in future development of a portable HIL system, to analyse chatter phenomena in the presence of cutting force nonlinearities and to test specific cutting tools before prototyping. Graphical abstract: Image 1 Highlights: Stability of machining processes is investigated in hardware-in-the-loop setup. The chatter frequency is influenced by the nonlinearity of the actuator force. The digressive character of the setup is revealed by stability tests.